Interpreting deindustrialised landscapes of Atlantic Canada: memory and industrial heritage in Sackville, New Brunswick. - Summerby-Murray, Robert (Canadian Geographer)
The redevelopment of former industrial sites now constitutes a significant component of the landscape of Atlantic Canada. This paper explores the heritage issues surrounding two industrial sites in Sackville, New Brunswick, and argues that the heritage discourse is constructed through the creation of memory and the processes of commodification and consumption. Using the examples of two foundries, the paper investigates the manner in which the image of industry has been presented and reinterpreted, both through the industrial heydays of the late-19th and mid-20th centuries and the contemporary scene. The commemoration, commodification and consumption of selected aspects of the industrial past are significant means by which Sackville creates its place identity. The resulting landscapes remain problematic, however, with a tendency to be overly romanticised and sanitised or at odds with contemporary images of Sackville's place identity. Le réaménagement d'anciennes friches industrielles constitute aujourd'hui une importante composante du paysage des provinces atlantiques du Canada. Le présent article explore les questions patrimoniales entourant deux sites de ce type à Sackville (Nouveau-Brunswick) et formule l'hypothèse que le discours à saveur patrimoniale repose sur la création d'une mémoire et des processus de réification et de consommation. À partir de deux fonderies utilisées comme exempie, l'article examine comment l'image de l'industrie a été présentée et réinterprétée, tant à l'époque de gloire de l'industrialisation de la fin du XIXe siècle et du milieu du XXe siècle que sur la scène contemporaine. La commémoration, la réification et la consommation d'aspects choisis du passé industriel constituent d'importants moyens par lesquels Sackville crée son identité. Les paysages qui en résultent demeurent problématiques et ont tendance à être exagérément romantiques et aseptisés, voire même contradictoires par rapport aux images contemporaines de l'identité de Sackville. Reprinted by permission of the publisher.